PRESERVATION OF MOTHER TONGUE AND STRATEGIES FOR ACQUIRING A NEW LANGUAGE - Axatova Mohinisoxon Hasan qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article explores the sociolinguistic and pedagogical aspects of preserving the mother tongue while acquiring a new language, particularly in multilingual and immigrant contexts. It examines strategies that individuals and communities employ to maintain native language proficiency alongside learning a new language. The paper highlights the role of family, educational institutions, digital media, and peer interactions in balancing bilingualism. It also discusses the cognitive, cultural, and social implications of these strategies.